The Incidence of Hepatitis C Virus Infections among People Screened in Governmental Health Care Facilities in 2018 in Iraq - Yasmeen J.Al-Bayaa1 , Zainab A. Hamid 1 , Ali H. Bayati2 , Sarmad M. Zeiny1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The HCV the objectives of this study were to estimate the incidence of HCV infection (anti-HCV antibodies) in Iraq. Methodology: The criteria for diagnosis of HCV infection included new seroconversion manifested by the presence of positive HCV antibodies by screening tests and ascertained this result by confirmatory assays in the year 2018. The patients with HCV positive seroconversion recorded before 2018 are excluded from HCV incidence in 2018. The primarily positive cases were tested by anti-HCV antibodies confirmatory test prior to recording as new HCV infected cases. A sample size of 97,290 persons from the all 18 Iraqi governorates was enrolled in this study. Results: Among 97,290 persons screened for HCV antibodies, 576 new HCV infections were recorded as newly infected with incidence rate of 5.9:1000 among all Iraqi governorates in 2018. The highest incidence was reported in Baghdad-Resafa, Diwaniya, and Sulaymaniyah, and they were 15.2:1000, 13.7:1000, and 13.2:1000 respectively; the lowest incidence rates were registered in Erbil, Diyala, and Najaf and the results were zero, 0.32, and 0.53 respectively. In all Iraqi governorates, the highest incidence of HCV infection was at the age group 15–45 years and the lowest was in age group 1-4 years. For the total 576 new HCV recorded infections, 296 were males and 280 were females, with male to female ratio of 1:1.1. Conclusion: The incidence rate of HCV infection is high among people screened for anti-HCV Abs in Iraq in the year 2018 especially in Baghdad-Resafa, nearly both genders are equally affected and HCV infection is mostly recorded in age group 15-45 years. The HCV screening program should be achieved in all regions of Iraq and for all the required population groups, and it should be a compulsory measure.